181k views
1 vote
Given f(x)= -3x^3 - 8x^2 - x + 8 andg(x)= 3x^3 - 6x^2 - 8x - 8What would (f-g)(x) and (f-g)(-1) be?

1 Answer

2 votes

In this case, we'll have to carry out several steps to find the solution.

Step 01:

data:

f(x)= -3x³ - 8x² - x + 8

g(x)= 3x³ - 6x² - 8x - 8

Step 02:

functions:

(f - g)(x):

(f - g)(x) = -3x³ - 8x² - x + 8 - (3x³ - 6x² - 8x - 8)

(f - g)(x) = -3x³ - 8x² - x + 8 - 3x³ + 6x² + 8x + 8

(f - g)(x) = - 6x³ - 2x² + 7x + 16

(f - g)(-1):

(f - g)(-1) = - 6(-1)³ - 2(-1)² + 7(-1) + 16

(f - g)(-1) = - 6(-1) - 2(1) + 7(-1) + 16

(f - g)(-1) = 6 - 2 - 7 + 16

(f - g)(-1) = 13

That is the full solution.

User Giacomo Catenazzi
by
5.1k points